Numerical simulation of two-phase flow in airlift pumps using the Physical Influence Scheme. (26th May 2010) - Hanafizadeh, Pedram; Saidi, M.H.; Darbandi, Masoud; Kebriaee, Azade
A new approach has been presented to solve gas-liquid flow numerically in vertical pipes of air-lift pumps. To improve modelling, a new strategy has been employed with the capability of coupling the continuity and momentum equations and enforcing the role of pressure directly in the continuity equation. This is achieved via applying a novel scheme called the Physical Influence Scheme (PIS). The current finite volume solution is compared with other available numerical solutions. Indeed, they are in fair agreement. However, the present predictions are far superior to those obtained from an existing simple method, which is widely used in airlift pump modelling.